Impact of pressmud application in reclamation of high RSC irrigation water induced soil sodification and sustaining rice (Oryza sativa) - wheat (Triticum aestivum) production in Indo-Gangetic Plains - SHEORAN, PARVENDER; KUMAR, ARVIND; KUMAR, ASHWANI; RAJU, R; SHARMA, RAMAN; PARJAPAT, KAILASH; BARMAN, ARIJIT; SINGH, RANJAY K; KUMAR, SATYENDRA; SHARMA, P C; CHAHAL, V P; SINGH, A K (The Indian Journal of Agricultural Sciences, 2020)
Farmers mostly prefer mineral gypsum as reclamation ameliorant for sodic soils. Timely availability of quality product many a times hampers the pace of reclamation process impairing crops productivity to a greater extent. To measure the reclamative efficiency of pressmud in sodic ecosystems dominating rice (Oryza sativa L.) - wheat (Triticum aestivum L.)system, a total of 37 farmer’s participatory trials were carried out in Kaithal district of Haryana state. Soil incorporation of pressmud at 10 t/ha improved the plants adaptation through significant improvement in agro-physiological and biochemical parameters of crop response. Concomitant reduction in spikelets sterility (~21%) and chaffy grains per panicle (~17%) in rice under pressmud ameliorated plots imparted yield advantage to the tune of ~21% under sodic conditions. In wheat, pressmud application increased productive tillers per mrl (13%), spikelets per spike (8%), grains per earhead (10%) and 1000-grain weight (2%) elucidating ~14% yield gain compared to farmer’s managed plots. System productivity in terms of wheat equivalent yield improved by ~15% per cent due to pressmud application under a variable range of soil pH (7.18-8.65) and RSCiw (1.6-7.6 me/L). Pressmud incorporation resulted in reduction of Na saturation in soil-plant continum and neutralized soil alkalinity with consequent reduction in soil pH to the extent of 0.07-0.44 units with a mean value of 8.47 after crop harvest against initial value of 8.68. Amelioration of sodic soils through pressmud application showed economic benefits of ₹ 24779 / ha with incremental benefit-cost ratio of 5.04 for each rupee invested against the added cost of ₹ 4920 / ha. Field application of pressmud not only ensured the safe disposal of this waste byproduct but also helped in achieving the sustainable yields. Evidences from farmer’s participatory trials revealed that pressmud can serve as affordable alternative amendment to gypsum in sodic land reclamation programme. In nutshell, scientific diagnosis of field problems, strong farmers-scientist interface and participatory research could work as suitable and location specific adaptive strategies in arresting the salt induced land degradation and strengthening farmers’ livelihood.